2013
DOI: 10.1007/s00044-013-0577-5
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiazole derivatives as human DNA topoisomerase IIα inhibitors

Abstract: Benzothiazole derivatives resembling the structure of DNA purine bases were tested to determine their topoisomerase inhibition activities. Based on DNA topoisomerase I and II relaxation assay results, all 12 derivatives acted as human topoisomerase IIa inhibitors, whereas only two compounds inhibited Calf thymus topoisomerase I. 3-amino-2-(2-bromobenzyl)-1,3-benzothiazol-3-ium 4-methylbenzensulfonate (BM3) was observed to be the most effective human topoisomerase IIa inhibitor with the lowest IC 50 value of 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…In this study, we used fast flexible docking to study the binding orientations and predict binding affinities of benzothiazole and benzothiazolium derivatives. Such studies have been carried out to understand the forms of interaction of 12 compounds, examined by Kaplan-Ozen and colleagues for human DNA topoisomerases [21]. The results obtained from this study will be useful in understanding the inhibitory mode of benzothiazole and benzothiazolium derivatives, as well as in rapidly and accurately predicting the activities of newly designed inhibitors on the basis of docking scores.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we used fast flexible docking to study the binding orientations and predict binding affinities of benzothiazole and benzothiazolium derivatives. Such studies have been carried out to understand the forms of interaction of 12 compounds, examined by Kaplan-Ozen and colleagues for human DNA topoisomerases [21]. The results obtained from this study will be useful in understanding the inhibitory mode of benzothiazole and benzothiazolium derivatives, as well as in rapidly and accurately predicting the activities of newly designed inhibitors on the basis of docking scores.…”
Section: Introductionmentioning
confidence: 99%
“…A set of previously synthesized benzothiazole and 3-amino-benzothiazolium derivatives [16] tested for DNA topoisomerase II inhibitory activity were chosen from our previous study [21] as shown in Table 1. The DNA topoisomerase II inhibitory activities of these compounds are represented as IC 50 values in the millimolar, micromolar or nanomolar range [21].…”
Section: Molecular Structures and Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the benzoxazole and benzamide compounds, which were previously synthesized in our laboratory, showed strong inhibitory activity for human DNA Topoisomerases and Glutathione S-Transferases and also anticancer effects observed on various cell cultures [12][13][14][15][16][17][18][19][20]. These findings encouraged us to search for the new anticancer target NK1R by comparing their activities with the well-known NK1R antagonist aprepitant.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade our group have been working on the drug design studies on the new anticancer active compounds by using both computational techniques and experimental work such as synthesis and activity studies [12][13][14][15][16][17][18][19][20]. Some of the benzoxazole and benzamide compounds, which were previously synthesized in our laboratory, showed strong inhibitory activity for human DNA Topoisomerases and Glutathione S-Transferases and also anticancer effects observed on various cell cultures [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%